TOGO TO GO: PRODUCTS AND COMPOUNDS DERIVED FROM LOCAL PLANTS FOR THE TREATMENT OF DISEASES ENDEMIC IN SUB-SAHARAN AFRICA - Tittikpina, Nassifatou Koko; Ejike, Chukwunonso ECC; Estevam, Ethiene Castelluci; Nasim, Muhammad Jawad; Griffin, Sharoon; Chaimbault, Patrick; Kirsch, Gilbert; Atakpama, Wouyo; Batawila, Komlan; Jacob, Claus (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Many African countries suffer from endemic diseases which are often caused by infections and seriously affect the social and economic development of these nations. While the access to proper medication is still limited, many of these countries are, at the same time, rich in medical plants. Materials and Methods: A review of relevant scientific (and gray) literature was carried out and information obtained from local authorities in medicinal plants. A synthesis of the data obtained was thereafter performed and recommendations for the future proposed. Results: Plants such as Cissus aralioides, Securidaca longipedunculata, Piliostigma thonningii, Nauclea latifolia, Ocimum gratissimum and Newbouldia laevis are widely reported to be used in the treatment of endemic diseases in Togo and her neighbouring countries.These plants often contain highly potent chemical compounds, such as quinones, xanthones, tannins and terpenes and therefore may provide an alternative avenue to short-term treatment. A combination of further analysis of plant materials and their active ingredients on the one hand, and modern technology to turn such natural products into commercial equivalents on the other, is required in order to identify the targets and modes of action of these natural materials, unlock access to them, and ultimately produce valuable medicines and phytoprotectants based on locally grown plant materials. Conclusion: The production of plant-derived products, as advocated in this paper, is in line with the WHO’s traditional medicine strategy 2014- 2023, and will eventually yield a sustainable health-and-wealth generating cycle that will benefit a countries in the region, economically and ecologically.